Park design influence on community’s participation in recreational activities at Persiaran Sembilang Public Recreation Park / Ilya Afiqah Ahmad Jihadi - Ahmad Jihadi, Ilya Afiqah (Universiti Teknologi Mara, Perak, 2021)
Recreation is a crucial activity that helps maintain good health and yet is always neglected. Usually active or passive recreation is done in a park because the space is wider and the environment is peaceful. The study was focused on a few issues and problems related to factors that contribute to the lack of visitor’s participation in recreational activities at Persiaran Sembilang Public Recreation Park. In order to achieve the study’s aim, some objectives were provided which include method such as identifying and analyzing the park’s visitors behavior and park’s elements, such as the facilities or access in order to understand fully the issue in the study area. Several methods are used to conduct the study which include handing out questionnaires, observation at the study area and interview session. The respondents are randomly selected, and the findings are obtained. The findings are used and analyzed in order to detect the issue. The information obtained from the study are used to come up with some recommendations that will help to improve the number of visitors participation in recreational activity at Persiaran Sembilang Public Recreation Park. by improving the facilities, attraction, safety and variety of new elements. In the end of this research, the park should be a place where people gather to spend their time, fulfilling the park’s provision main purpose.